OECD sovereign borrowing outlook 2009 - Blommestein, Hans J.. (OECD Publishing, 2009)
Many OECD governments are facing unprecedented challenges in the markets for bonds and bills, as a result of the explosive growth in their borrowing needs. Amidst an unusually uncertain economic outlook, the gross borrowing needs of OECD governments are expected to reach almost USD 12 trillion in 2009. The key policy issue is how to raise smoothly new funds at low cost, while also managing a rapidly growing debt stock. For the time being, several factors are offsetting the trend towards higher yields. But the risk is that when the recovery gains traction and risk aversion falls, yields will start to rise. There are already signs that issuance conditions are becoming tougher with reports of weaker demand at some recent government bond auncts. Thus far, these less successful auctions can best be interpreted as "single market events" and not as unambiguous evidence of systemic market absorption problems. Also from this perspective lowering OECD sovereign ratings is not obvious. The future could become more challenging, given that rising issuance is occurring in tandem with increasing overall debt levels. Also contingent debt is on the rise. In response, sovereign debt managers have begun to plan or implement credible medium-terms exit strategies to avoid future "crowding out" and issuance problems. Although fund raising strategies have become more flexible and somewhat more opportunistic, OECD debt management framework so as to minimise medium-term borrowing costs. The other key challenge, roll-over risk as a result of the increasing use of short-term instruments, is being addressed by OECD debt managers by rebalancing the profile of their issuance programmes by incorporating more long-term instruments